PENGARUH KUALITAS AUDIT DAN KONDISI KEUANGAN TERHADAP OPINI AUDIT GOING CONCER PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA - Nurlaelah Nurlaelah; Ela Nurlaelah (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2022)
Going concern audit opinion is an opinion that has been issued by the auditor to ascertain whether the company can maintain the company's viability for at least the next year. The going concern opinion received by a company indicates that there are conditions and events that raise the auditor's doubts about the viability of the company. Going concern audit opinion can also be used as an early warning for users of financial statements to avoid mistakes for decision making in the company.This study aims to determine the effect of Audit Quality and Financial Condition on Going Concern Audit Opinions in Manufacturing Companies in the Basic and Chemical Industry Sector listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The method used in this study is a quantitative method, the population in this study is 75 companies, then the sample is determined using purposive sampling technique and the sample is 15 companies. The method used in this analysis is Logistic Regression Analysis using SPSS V.25 application. In this study it can be shown that: (1) Audit quality has no significant effect on the Going Concern Audit Opinion. (2) Financial condition has no significant effect on Going Concern Audit Opinion. (3) Audit Quality and Financial Condition simultaneously have no significant effect on Going Concern Audit Opinion.